Proteomic analysis of the skeletal muscles from dysferlinopathy patients. (January 2020) - Choi, Young-Chul; Hong, Ji-Man; Park, Kee Duk; Shin, Ha Young; Kim, Seung Min; Park, Hyung Jun
Highlights: Proteomic analysis revealed altered protein expression pattern in dysferlinopathy. Two-dimensional electrophoresis revealed 44 spots with different volume. Liquid chromatography-mass spectrometry revealed 26 differently expressed proteins. Western blotting revealed elevated expression of three proteins in dysferlinopathy. Abstract: Dysferlinopathy is an autosomal recessive disease caused by pathogenic variants in DYSF gene. We compared muscle protein extracts from dysferlinopathy patients and control subjects to identify new biomarkers of this myopathy. We reviewed the medical records from January 2002 to October 2016. Eight vastus lateralis muscle samples from five dysferlinopathy patients and three control subjects were selected. We separated proteins/peptides from all eight muscle protein extracts using two-dimensional electrophoresis (2DE). Data were acquired from liquid chromatography-mass spectrometry protein fragmentation patterns after comparing the spot volumes. Western blotting revealed total dysferlin loss in the dysferlinopathy patients but normal expression in the control subjects. 2DE indicated somewhat diverse protein constellations between the dysferlinopathy and control groups. Image analysis showed that 80 spots were differently expressed between two dysferlinopathy and one control samples. We selected 44 spots with consistently different volume between dysferlinopathy and control groups. Liquid chromatography-mass spectrometry indicated 26 differently expressed proteins. Western blotting revealed that creatine kinase M-type, carbonic anhydrase III (muscle specific) and desmin were significantly elevated in dysferlinopathy muscle. Additionally, four proteins (myosin light chain 1/3, skeletal muscle isoform; lamin A/C; ankyrin repeat domain 2; and eukaryotic translation initiation factor 5A-1) were inconsistently elevated in the dysferlinopathy samples. We confirmed the usefulness of the classic biomarker and have newly identified the altered expression of proteins in the skeletal muscles of dysferlinopathy patients.